An Aquaculture Water Checker--design and Manufacture - Anh, Nguyen Tuan; Cu, Dang Xuan; Bao, Phung Quoc; Phi, Vu Anh; Duong, Bach Gia (Communications in Physics, 2012)
A real-time, mobile aquaculture water checker is presented. The configuration of double integrating spheres is developed for simultaneously measuring backward scattering $R_d$, forward scattering $T_d$ and transmitted light $T_c $. Based on Kubelka-Munk model, a set of optical parameters including absorption coefficient $μ _a $, scattering coefficient $μ_s$ and anisotropy $g$ are calculated. The obtained results for diluted milk standard samples with different milk concentrations and aquaculture water samples with different densities of Psexdo-Nitzschia-delicatissium algae are also reported.